Phytochemical Composition and Toxicological Screening of Anise Myrtle and Lemon Myrtle Using Zebrafish Larvae - Paolin Rocio Cáceres-Vélez; Akhtar Ali; Alexandre Fournier-Level; Frank R. Dunshea; Patricia Regina Jusuf (MDPI AG, 2024)
Plants are an immense source of drugs, and 50% of modern pharmacopeia has a plant origin. With increasing life expectancy in humans, many age-related degenerative diseases converge on oxidative cellular stress pathways. This provides an opportunity to develop broad treatments by targeting the cause of common pathologic cell degeneration. Toxicological effects can be readily assessed in a live animal model system to establish potential fauna for clinical use. Here, we characterized and evaluated the antioxidant potential and toxicological effects of anise myrtle (Syzygium anisatum) and lemon myrtle (Backhousia citriodora) leaves. Using zebrafish larvae, a model for high-throughput pre-clinical in vivo toxicology screening, we identified safe levels of extract exposures for development of future therapeutics. The antioxidant capacity and toxicity were very similar in these two myrtles. The LC50-96h for anise myrtle was 284 mg/L, and for lemon myrtle, it was 270 mg/L. These measurements are comparable to ongoing studies we are performing using the same criteria in zebrafish, which allow for robust testing and prioritization of natural fauna for drug development.